2018
DOI: 10.1089/lap.2017.0744
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Biliary Drainage Versus Percutaneous Transhepatic Biliary Drainage in Patients with Resectable Hilar Cholangiocarcinoma: A Systematic Review and Meta-Analysis

Abstract: For patients with obstructive jaundice associated with HCCA, current evidence indicate no superiority of PTBD over EBD regarding clinical feasibility and success rate, but data suggest a better clinical safety of PTBD compared with EBD in short-term postoperation. In long-term evaluation, the differences in clinical outcomes are not statistically significant between PTBD and EBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 28 publications
2
31
1
2
Order By: Relevance
“…Recent meta-analyses comparing the endoscopic biliary drainage with percutaneous transhepatic approach have found that patients received mainly an endoscopic drainage (52% -63.5%) (36;63;64). However, the percutaneous approach was associated with significantly decreased morbidity rates, including cholangitis and acute pancreatitis (36,39,64). No differences of liver failure, hemorrhage and overall survival rates were observed between the groups (39,(63)(64)(65).…”
Section: Discussion Discussionmentioning
confidence: 98%
“…Recent meta-analyses comparing the endoscopic biliary drainage with percutaneous transhepatic approach have found that patients received mainly an endoscopic drainage (52% -63.5%) (36;63;64). However, the percutaneous approach was associated with significantly decreased morbidity rates, including cholangitis and acute pancreatitis (36,39,64). No differences of liver failure, hemorrhage and overall survival rates were observed between the groups (39,(63)(64)(65).…”
Section: Discussion Discussionmentioning
confidence: 98%
“…Transpapillary stent placement with endoscopic retrograde cholangiopancreatography has been the preferred treatment modality for the palliation of malignant distal biliary obstruction [3,19]. However, the performance in patients with resectable tumors is unclear.…”
Section: Endoscopic Biliary Drainagementioning
confidence: 99%
“…Success rates of the initial procedure ranged from 24 to 78%. Although the discomfort of the patient is imposed by nasal drainage, endoscopic nasobiliary drainage is a better way to improve the durability and reduce cholangitis than endobiliary stenting [3].…”
Section: Advantagesmentioning
confidence: 99%
See 2 more Smart Citations